External auditory canal cholesteatoma: 20 years of experience - Federico Herranz; Julián Agustín Simkin; Federico Di Lella; Gabriela Perez Raffo (Brazilian Journal of Otorhinolaryngology, 2025)
Objective(s): To determine the prevalence of external auditory canal cholesteatoma in the Otolaryngology service of the Hospital Italiano de Buenos Aires, and to evaluate the therapeutic approaches and their outcomes. Methods: A retrospective review was conducted of the electronic medical records of adult patients diagnosed with external auditory canal cholesteatoma between August 2004 and April 2024. Inclusion criteria were a confirmed or presumptive diagnosis of external auditory canal cholesteatoma and a minimum follow-up of six months. Variables analyzed included age, sex, disease severity (classified using the Udayabhanu HN 2018 classification), laterality, therapeutic approach, recurrence, and follow-up duration. Results: Fifty-two patients met the inclusion criteria, with an average age of 60.3 years. Most were female (57.7%). Bilateral involvement occurred in 5.8% of cases, and 86.5% of external auditory canal cholesteatoma were primary. According to the Udayabhanu HN classification, 28.8% were grade I, 63.5% were grade II, and 7.7% were grade IIIa. Conservative treatment was administered to 53.8% of patients, while 46.2% underwent surgery. The majority of surgical patients (58.3%) received canaloplasty and reconstruction, while 33.3% underwent only canaloplasty. Canaloplasty with mastoidectomy and meatoplasty was performed in 8.3% of cases. One patient experienced recurrence 13 years post-surgery. Conclusion(s): Both surgical and conservative treatments for external auditory canal cholesteatoma can lead to successful outcomes. The therapeutic approach should be tailored to the stage of the disease and patient characteristics, with early diagnosis and appropriate management essential to preventing complications. Level of evidence: 4.